Mob school survivor - Mann, Greyson; Brack, Amanda (New York : Sky Pony Press, 2017)
"Gerald Creeper Jr. is a self-proclaimed pacifist, but he finds himself in the war zone when he starts his first year at Mob Middle School. At his new school, every monster in the Overworld is jockeying for power, and the skeletons seem to have it out for him. Armed with a 30-day plan, Gerald makes it his mission to use his brains--instead of his blasts--to survive the school year"-- Provided by publisher.
"An unofficial Minecrafter's novel"--Cover.
Keywords: Minecraft (Game) -- Juvenile fiction; Monsters -- Juvenile fiction; Bullying -- Juvenile fiction; Schools -- Juvenile fiction; Adventure stories; Minecraft (Game) -- Fiction; Monsters -- Fiction; Bullying -- Fiction; Schools -- Fiction; Adventure and adventurers -- Fiction